The future of the cultural workforce: Perspectives from early career arts professionals on the challenges and future of the cultural industries in the context of COVID-19. Issue 1 (2022) - Shaughnessy, Caitlin; Perkins, Rosie; Spiro, Neta; Waddell, George; Campbell, Aifric; Williamon, Aaron
Abstract: The COVID-19 pandemic has had a profound impact on the arts sector, disrupting livelihoods and professional networks and accentuating the instability that is common for creative workers. Gaps in support for grassroots organisations and freelance workers have highlighted structural inequalities within the industry, and the significant challenges for individual workers in the early stages of their career. Yet, the pandemic has also emphasised the importance of the arts as a community resource and its role in supporting wellbeing and togetherness. This qualitative study explored the experiences of the pandemic for early career arts workers, focusing on its impacts upon their livelihoods and how it has shaped their future career directions. Sixteen arts and cultural workers across a variety of sectors including theatre, film, circus, music, and literature participated in solo, semi-structured interviews during April–June 2021. Thematic analysis identified three overarching themes: (i) 'Pandemic precarity and creative practice', (ii) 'PostCOVID I: Inclusivity and diversifying audiences', and (iii) 'PostCOVID II: Adapting, developing, and disrupting cultural practices'. Overall, the experiences capture an early career workforce that, while committed and engaged with their creative practice, also seeks a more equitable, fairer, and diverse industry that protects artists and engages more flexibly with broader audiences.